Department of Physiology, All India Institute of Medical Sciences (AIIMS), Madurai. (Journal of Forensic Medicine & Toxicology, 2022)
Background: The high global incidence of suicides has constrained researchers to improve methods to study the genome underlying suicide behavior in various populations worldwide. Aim: This paper intends to identify ways for the possible prevention, or at least reduction in rate of suicides by reviewing latest advances in research on molecular changes in the genome of suicide attempters. Methodology: Articles indexed in PubMed, Scopus and Google Scholar and those related to genetic research in suicidal behavior were reviewed from the years 2016 - 2021. Genetic and epigenetic changes in suicide behavior were divided into neurotrophic system metabolism, neurotransmission, neuro-endocrine and neuro inflammation. Results: The data related to long-term studies like GWAS provided reliable information but indicated for more detailed research in future. Little data was found about the association of genetic changes with suicidal behavior other than that related to underlying psychiatric disorders. The vast majority of available studies used samples from living persons who had suicidal ideation or attempts. Therefore, authors dwelled about the application of existing knowledge about the genetics of those who manifested suicidal behavior or ideation to identify and prevent suicide in population at risk via translational research. Authors propose conduction of studies related to genetic changes in cases of completed suicide but without history of underlying psychiatric disorders. The role of altered lipid profile and suffering from cancer in the genesis of suicidal ideation is really equally interesting, as it is seen for few other novel factors.
Keywords: Suicide; Suicidal behavior; Suicidal attempt; Human genetics; Epigenetic; GWAS